Complications of Percutaneous Endoscopic Gastrostomy in Children: A Single Centre Experience - İshak Abdurrahman Işık; Ulaş Emre Akbulut; Atike Atalay; Hasan Serdar Kıhtır; Yasin Bayram (Galenos Yayinevi, 2021)
Aim:The aim of this study was to investigate the complications of percutaneous endoscopic gastrostomy in children.Materials and Methods:Ninety-one pediatric patients treated with percutaneous endoscopic gastrostomy (PEG) insertion by pull technique in a five-year period were enrolled into this study. Their hospital records were reviewed retrospectively for their demographic data, their primary diseases causing nutritional insufficiency, and any major or minor complications after PEG insertion.Results:The 91 patients who were included in this study were aged between 1 month and 18 years (median 79 months). 45.1% (n=41) of the patients were female. The majority of the patients (76.9%, n=70) had neurological diseases. Nineteen patients (20.9%) had metabolic diseases and two patients had cystic fibrosis (2.2%). We observed 37 (40.7%) complications in total. Three (3.3%) of them were major and 34 (37.4%) of them were minor complications.Conclusion:Endoscopic percutaneous gastrostomy placement is an important way to continue enteral feeding in children. Although PEG is a minimally invasive technique, there are some problems which may be experienced by the children and their parents after PEG insertion, the majority of the these being minor complications.